The Adoption of Ar-Rahnu and Financial Wellbeing of Microentrepreneurs in Malaysia - Azman, Nik Hadiyan Nik; Zabri, Mohd Zaidi Md; Masron, Tajul Ariffin; Malim, Nurhafiza Abdul Kader (Human Resource Management Academic Research Society, 2020)
There is an urgent call for a potential justification on how and to what extent customers (microentrepreneurs) of Ar-Rahnu institutions in Malaysia are successfully driven their living standards from B10 (hardcore poverty) to B40 (low income). This study classified Ar-Rahnu’s adoption factors into three categories, namely, Shari’ah governance, uniqueness of Ar-Rahnu, and efficiency. 150 questionnaires were distributed to micro-entrepreneurs that used Ar-Rahnu and analysed using SmartPLS 3.0. Based on the results, it shows that Shari’ah governance has a low correlation and insignificant relationship towards Ar-Rahnu adoption. Stated differently, it means that customers find Shari’ah-compliance requirements not as important and it does not get in their way of getting instant cash from Ar-Rahnu. The other two constructs, namely as uniqueness and efficiency, have positive relationships with Ar-Rahnu adoption. It shows a significant and positive relationship with the Ar- Rahnu financing output. Unlike previous studies within the body of knowledge that mainly focuses on the adoption factors of Ar-Rahnu, this study went a step further by addressing the after-effect or impact of Ar-Rahnu adoption towards customers’ wellbeing, especially in terms of financial wellbeing and have found positive results.